Sources of cumulative continuity in personality a longitudinal multiple-rater twin study. [article]. - Kandler, Christian
This study analyzed the etiology of rank-order stability and change in personality over a time of 13 years in order to explain cumulative continuity with age. NEO five-factor inventory self-and peer report data from 696 monozygotic and 387 dizygotic twin pairs reare3d together were analyzed using a combination of multiple-rater twin, latent state-traits, and auto regressive simplex models. Correcting for measurements error, this model disentangled genetic and environmental affects on a long- and a short-term convergent valid stability, on occasional influences, and on self-and peer report-specific stability. Genetic factors represented the main sources that contributed to phenotypic long-term stability of personality in young and middle adulthood, whereas change was predominantly attributable to environmental factors. Phenotypic continuity increased as a function of cumulative environmental effects which became manifest in stable trait variance and decreasing occasion-specific effects with age. This study's findings suggest a complex interplay between genetic and environmental factors resulting in the typical patterns of continuity in personality across young and middle adulthood.
Keywords: Personality; Continuity; Genetics; Environment; Twin study